PROFILE OF THE BODY COMPOSITION, OF THE SOMATOTYPE AND BASIC PHYSICAL QUALITIES OF SURFERS OPEN CATEGORY OF THE PARAÍBA (Fiep Bulletin - online, 2014)
Objective: to establish the profile of the body composition, the somatotype, and basic physical qualities of surfers of the Open category of the Paraíba. It is a study of the transversal and descriptive type. Sample: 30 athletes, being 6 adolescents and 24 adults of both the sexes. Was adopted for evaluation of the body composition the Body Mass Index (BMI) and the Percentage of Fat (%G) according to Deuremberg (1980) for adolescents and Jackson, Pollock and Ward (1978/1980) for adults. It was used the somatotypical protocol of Heath & Carter (1990) and the referring tests to the evaluation of the physical qualities: Flexibility (FLEX), Agility (AGILE), Power (PO) = vertical Impulse (IV) and horizontal Impulse (IH), Located muscular resistance (RML) = Support of front on the ground (AF) and Abdominal (ABD) and Aerobic resistance. For the analysis of the data it was used SPSS 14.0. Results: it had significant difference in the percentage of fat (%f) and vertical impulse (IV) between the sexes (adolescents) (p < 0,05). The adolescents had presented one BMI and one %G inside of the stipulated standards of references. The boys had presented one Somatotype Mesomorfic balanced (2,4 - 6,3 - 2,4) and girls one Somatotype central (3,3 - 3,8 - 3,5). How much to the physical qualities, the boys had presented below of the average: ABD (34,3reps; average = 37reps), IV (39,1cm; average = 43,53cm), IH (196,0cm; average = 211,7cm), AGILE (12,16seg; average = 10,53seg) and RAER (32,97ml/kg/min; very weak), while the girls had presented IV (28,1cm; average = 28,38), AGILE (15,52seg; average = 12,26seg) and RAER (27,82ml/kg/min; weak). Between the adults, it had significant difference in the weight, stature, percentage of fat (%f), Endo e Aerobic resistance (RAER) between the sexes (p < 0,05). These had presented one BMI and one %G inside of the stipulated standards of references. The men had presented one Somatotype Mesomorfic balanced (2.1 - 4,9 - 2,2) and women one Somatotype Mesomorfic- Endomorfic (4,2 - 4,7 - 2,3). In the physical qualities, the men had presented only IV below of the average (42,80cm; average = 45,8cm), while the women had presented only IH (215,0cm; Weak). Although with an adjusted body composition, physical qualities had been observed below of the values standards preset in literature. These facts evidence that it must have a program of trainings where can give to greater attention to these variable.
Keywords: Surf; Body composition; Somatotype; Physical capacity